2008
DOI: 10.1590/s1678-77572008000400008
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a new toothbrush design versus a conventional tongue scraper in improving breath odor and reducing tongue microbiota

Abstract: For centuries, specific instruments or regular toothbrushes have routinely been used to remove tongue biofilm and improve breath odor. Toothbrushes with a tongue scraper on the back of their head have recently been introduced to the market. The present study compared the effectiveness of a manual toothbrush with this new design, i.e., possessing a tongue scraper, and a commercial tongue scraper in improving breath odor and reducing the aerobic and anaerobic microbiota of tongue surface. The evaluations occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
17

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 22 publications
(43 reference statements)
2
34
1
17
Order By: Relevance
“…The TC is a visible white-brownish layer adherent to the dorsum of the tongue, consisting of desquamated epithelial cells, blood cells, metabolites, nutrients, and bacteria [9,10]. Therefore, any factors that are involved in the disability of keratinization and apoptosis of epithelial cells of the tongue [11], blood cell infiltration, erythrocyte diapedesis, and complex microbial colonization will have a profound effect on the metabolites and nutrients that are the main causes for TC formation.…”
Section: Biology Of the Tongue Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…The TC is a visible white-brownish layer adherent to the dorsum of the tongue, consisting of desquamated epithelial cells, blood cells, metabolites, nutrients, and bacteria [9,10]. Therefore, any factors that are involved in the disability of keratinization and apoptosis of epithelial cells of the tongue [11], blood cell infiltration, erythrocyte diapedesis, and complex microbial colonization will have a profound effect on the metabolites and nutrients that are the main causes for TC formation.…”
Section: Biology Of the Tongue Coatingmentioning
confidence: 99%
“…Casemiro et al [9] summarized the microbial species isolated from the tongue, which included Porphyromonas gingivitis , Aggregatibacter actinomycetemcomitans , members of the Spirochaetes , Prevotella intermedia , and Capnocytophaga spp. In recent studies it has been verified that the microbiome of the human body is associated with the human physiology, pathophysiology, and health status [24].…”
Section: Biology Of the Tongue Coatingmentioning
confidence: 99%
“…There are several studies suggesting that tongue cleaning/scraping can reduce the levels of VSCs in exhaled air (Lee et al 2003, Casemiro et al 2008, Tsai et al 2008, Pham et al 2011, Lu et al 2014. One published review of the literature reported that the efficacy of tongue cleaning/scraping is conflicting (Van der Sleen et al 2010) whereas another systematic review demonstrated that there was a minor superiority of tongue scrapers as compared to brushing in reducing halitosis (Outhouse et al 2006).…”
Section: Tongue Cleaningmentioning
confidence: 99%
“…The evaluated methods were equally effective in the improving breath odour and reducing the facultative aerobic and anaerobic microbiota on tongue surface of the studied population. 73 Carvalho MD et al demonstrated the beneficial impact of mouthrinses on morning breath even in the absence of mechanical plaque control. In a cross-over trial on college students, the VSC formation was inhibited in descending order, 0.2% chlorhexidine, 0.12% chlorhexidine, triclosan and essential oils and cetylpyridinium chloride.…”
Section: Treatmentmentioning
confidence: 99%